Analysis of Marketing Performance: A Case Study of Rice Marketing at Usaha Dagang Hardianti, Pinrang Regency - Mutlak, Fuji Dariani; Saleh, Muh. Ikmal; Molla, Saleh; Nadir (Program Studi Agribisnis Universitas Muhammadiyah Sinjai, 2025)
This study is intended to analyze the influence of product quality, selling price, distribution location, and marketing strategies on the marketing performance of rice at Usaha Dagang Hardianti in Pinrang Regency. The approach used is quantitative, employing multiple linear regression analysis. Data were collected through questionnaires, interviews, and documentation studies, and were analyzed using validity and reliability tests, t-test, F-test, and the coefficient of determination (R²). The findings indicate that only the distribution location and selling price variables have a significant effect on marketing performance, with significance values of 0.025 and 0.041 respectively—both below the 0.05 threshold. In contrast, the product quality and promotional strategy variables do not show significant influence, with significance values of 0.892 and 0.275 respectively (>0.05). The coefficient of determination (R²) reveals that the independent variables account for only 22.3% of the variation in marketing performance, while the remaining 77.7% is influenced by other factors outside the model. These findings highlight that competitive pricing and distribution efficiency play a more dominant role in enhancing marketing performance than product quality or promotional efforts. Therefore, business actors are advised to prioritize the implementation of competitive pricing strategies and optimal distribution systems to strengthen the market competitiveness of their rice products.